Preparation method of high-conductivity lithium-conductivity composite aqueous binder for high-voltage positive electrode material

By using a highly conductive lithium composite water-based binder, using the combination of carrageenan, sodium carboxymethylcellulose and pyrrole monomer, the problems of low conductivity and poor lithium ion diffusion kinetics of lithium-rich manganese-based positive electrode materials are solved. Achieve high energy density and long life battery performance.

CN119391359APending Publication Date: 2025-02-07XIAN TECH UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411290141.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-14
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

Lithium-rich manganese-based cathode materials have problems with low conductivity and poor lithium ion diffusion kinetics, resulting in low efficiency and poor circulation and rate performance for the first time, limiting their commercial applications.

Method used

A method of preparing a highly conductive lithium composite water-based binder consisting of carrageenan, sodium carboxymethylcellulose and pyrrole monomer, obtained by solution mixing and initiating polymerization, and has high lithium ion mobility and electronic conductivity.

Benefits of technology

This binder significantly improves the first-circle Coulomb efficiency and long-cycle performance of the electrode, achieving a lithium-rich manganese battery with high energy density and long life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119391359A_ABST
    Figure CN119391359A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of a high-conductivity lithium composite aqueous binder for a high-voltage positive electrode material, which comprises the following steps: adding carrageenan into deionized water, uniformly mixing, adding sodium carboxymethyl cellulose, and stirring and mixing at room temperature for 24 hours to prepare a carrageenan-sodium carboxymethyl cellulose solution; and adding a pyrrole monomer into the carrageenan-sodium carboxymethyl cellulose solution, stirring and mixing for 5 minutes at room temperature, adding an initiator, stirring overnight at room temperature, and polymerizing to obtain the high-conductivity lithium-conductivity composite aqueous composite binder. According to the binder prepared by the invention, the conductivity and lithium conduction performance of the binder are bidirectionally improved, multi-electron transfer of an active material is excited, and the lithium ion transport stability is improved, so that the first-circle coulombic efficiency and long cycle performance of an electrode are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention is applied to the field of new energy secondary batteries, namely, a binder for high-voltage positive electrode materials of lithium-ion batteries, and specifically relates to a method for preparing a highly conductive and lithium-conductive composite aqueous binder for high-voltage positive electrode materials. Background Art

[0002] As an important secondary clean energy source, lithium-ion batteries are widely used in power equipment, automobiles and large-scale energy storage systems. However, the key to achieving its sustainable development lies in the development of cathode materials with high energy density and long cycle life. Lithium-rich manganese-based cathode materials are expected to become the new generation of high energy density lithium-ion cathode materials due to their high specific capacity and low cost.

[0003] At present, lithium-rich manganese-based cathode materials have problems of low conductivity and poor lithium ion diffusion kinetics, which directly lead to low first coulombic efficiency, poor cycle and rate performance, thus limiting their commercial application. Although researchers have made many attempts in surface modification, ion doping and structural optimization to improve the electrochemical properties of lithium-rich materials, the effects of these measures are still not enough to meet the needs of large-scale applications.

[0004] The electrochemical reaction of lithium-ion batteries mainly occurs at the interface between the electrode and the electrolyte, so the composition of the electrode has an important influence on the battery performance. As a key component of the electrode, the binder has a small mass proportion (<5wt%) and low cost (<2%), but it plays a vital role in maintaining the mechanical integrity of the electrode network, ensuring cycle stability and rate performance.

[0005] Traditional lithium battery pole pieces are prepared using N-methylpyrrolidone (NMP) as solvent and polyvinylidene fluoride (PVDF) as binder, which is expensive and toxic, increasing the cost of material recovery and recycling. In recent years, researchers have been committed to developing natural or cross-linked modified water-soluble polymer binders to improve electrochemical performance and reduce environmental pollution. However, most current research focuses on the bonding and mechanical properties of binders, while research on kinetic modifications is relatively scarce; the electronic conductivity and ionic conductivity of lithium-rich manganese-based positive electrode materials are much lower than other materials such as lithium cobalt oxide, which requires the binder to be designed with high lithium ion mobility and electronic conductivity to minimize the adverse effects on electronic and ionic conduction in the electrode. Summary of the invention

[0006] The technical problem to be solved by the present invention is to provide a method for preparing a high-conductivity lithium-conductive composite aqueous binder for high-voltage positive electrode materials with high lithium ion migration and electronic conductivity, which is suitable for high-voltage lithium-rich positive electrode materials and has high energy density and long cycle life.

[0007] The technical solution of the present invention is:

[0008] A method for preparing a highly conductive lithium-conductive composite aqueous binder for high-voltage positive electrode materials, the specific steps of which are as follows:

[0009] Step 1: Prepare carrageenan-sodium carboxymethyl cellulose solution

[0010] Add carrageenan to deionized water, mix well, then add sodium carboxymethyl cellulose, the mass ratio of carrageenan, sodium carboxymethyl cellulose and deionized water is 1:1:98, stir and mix at room temperature for 24 hours to prepare a carrageenan-sodium carboxymethyl cellulose solution;

[0011] Step 2: Preparation of high-conductivity lithium-conducting composite binder

[0012] Take carrageenan-sodium carboxymethyl cellulose solution and add pyrrole monomer, the mass volume ratio of the carrageenan-sodium carboxymethyl cellulose solution to the pyrrole monomer is 100:2g / mL, stir and mix at room temperature for 5 minutes, add initiator, the mass ratio of the initiator to the carrageenan-sodium carboxymethyl cellulose solution is 1:100, stir and polymerize at room temperature overnight to obtain a high-conductivity lithium-conducting composite water-based composite binder.

[0013] Furthermore, the initiator is ammonium sulfate.

[0014] Furthermore, during the stirring and mixing, the stirring speed is 300 rpm.

[0015] Further, the mixture was stirred at room temperature overnight for 12 h.

[0016] The invention discloses an application of a water-based binder in a positive electrode sheet of a lithium-ion battery.

[0017] Furthermore, the lithium-ion battery positive electrode plate is a lithium-manganese-rich positive electrode plate.

[0018] Furthermore, the preparation of the positive electrode plate of the lithium-ion battery is as follows:

[0019] The active material, conductive agent and binder are uniformly mixed to form a slurry, which is then coated on an aluminum foil and dried in a vacuum oven at 110° C. for 20 hours to obtain a lithium-rich manganese-based positive electrode sheet.

[0020] Furthermore, the mass ratio of the active material, the conductive agent and the binder is 85:5:10.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] (1) The preparation method of the present invention is relatively simple. An excellent binder can be obtained by solution mixing and initiating polymerization without complicated post-processing steps, thereby reducing production costs and improving production efficiency.

[0023] (2) The use of water-based binders avoids the pollution caused by traditional organic solvents and achieves green production.

[0024] (3) The introduction of ionizable sulfonic acid groups into carrageenan makes carrageenan have better ionic conductivity after dissolving in water. By increasing the number and rate of lithium ion migration, the stability of lithium ion transport is improved, and fast charging of lithium ion batteries is achieved.

[0025] (4) The conductive polymer formed by the polymerization initiated by the pyrrole monomer of the present invention has good electronic conductivity and can effectively transmit electrons during the electrode cycle, thereby reducing the resistance to electron transmission. In addition, the interaction between the conductive polymer and the functional groups on the polyelectrolyte (such as ionic bonds, hydrogen bonds, covalent bonds, etc.) further enhances the bonding performance and mechanical stability of the electrode, thereby extending the service life of the battery.

[0026] In summary, the binder prepared by the present invention bidirectionally improves the electrical conductivity and lithium conductivity of the binder, stimulates the multi-electron transfer of the active material, and improves the lithium ion transport stability, thereby improving the first-cycle coulomb efficiency and long-cycle performance of the electrode, and realizing the development and application of high-energy density and long-life lithium-manganese-rich batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is a graph of the first charge and discharge curve at 30° C. and 0.1C rate after assembling a battery based on a modified binder lithium-rich manganese-based positive electrode material according to Comparative Example 3 of the present invention;

[0028] Figure 2 This is a discharge capacity decay diagram of a battery assembled with a modified binder-rich lithium manganese-based positive electrode material and cycled for 300 cycles at 30° C. and 1C according to Comparative Example 3 of the present invention;

[0029] Figure 3 The electrochemical impedance diagram of the battery assembled based on the modified binder lithium-rich manganese-based positive electrode material according to Comparative Example 3 of the present invention;

[0030] Figure 4 The first charge and discharge curve at 30°C and 0.1C rate after assembling a battery based on a modified binder lithium-rich manganese-based positive electrode material according to embodiment 1 of the present invention;

[0031] Figure 5 This is a discharge specific capacity decay diagram of a battery assembled with a modified binder lithium-manganese-based positive electrode material according to Example 1 of the present invention and cycled for 300 cycles at 30°C 1C;

[0032] Figure 6 The electrochemical impedance diagram of the battery assembled based on the modified binder lithium-rich manganese-based positive electrode material according to Example 1 of the present invention;

[0033] Figure 7 TEM image of the lithium-rich manganese-based positive electrode material prepared based on the modified binder according to Example 1 of the present invention;

[0034] Figure 8 This is a graph showing the first charge and discharge curve at 30°C and 0.1C rate after assembling a battery made of the product of Comparative Example 1 of the present invention;

[0035] Fig. 9 This is a discharge capacity decay diagram of a battery assembled from the product of Comparative Example 1 of the present invention after 300 cycles at 30°C 1C;

[0036] Fig.10 This is the electrochemical impedance diagram of the battery assembled from the product prepared in Comparative Example 1 of the present invention;

[0037] Fig.11 This is a TEM image of the product prepared in Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0038] The specific implementation method of the present invention is further described below in conjunction with examples. It should be noted here that the specific implementation method described here is only for illustrating and explaining the present invention and is not intended to limit the scope of protection of the present invention.

[0039] Example 1

[0040] Step 1: Add 1 g of carrageenan and 1 g of sodium carboxymethyl cellulose stepwise into 98 g of deionized water, and stir at 300 rpm for 24 hours at room temperature to prepare a uniform and transparent carrageenan-sodium carboxymethyl cellulose solution;

[0041] Step 2: Take 1g of carrageenan-sodium carboxymethyl cellulose solution, add 20μL of pyrrole monomer, stir at 300rpm for 5 minutes, then add 10mg of ammonium sulfate and stir at 50rpm overnight (12h) at room temperature for polymerization to obtain a highly conductive and lithium-conductive composite binder;

[0042] Step 3: Lithium-rich manganese positive electrode material 0.5Li2MnO3·0.5LiNi 0.33 Co 0.33 Mn 0.33 O2, conductive agent SuperP, and highly conductive and lithium-conductive composite binder are uniformly mixed in a mass ratio of 85:5:10 to prepare a slurry, coated on an aluminum foil current collector, and dried in a vacuum oven at 110°C for 20 hours. The resulting pieces are then cut to obtain lithium-rich manganese-based positive electrode sheets, denoted as P-CC11.

[0043] Comparative Example 1

[0044] Step 1: dissolving sodium carboxymethyl cellulose in deionized water and stirring for 24 hours to obtain a sodium carboxymethyl cellulose solution;

[0045] Step 2: Use the prepared sodium carboxymethyl cellulose solution as a binder and the lithium-rich manganese positive electrode material 0.5Li2MnO3·0.5LiNi 0.33 Co 0.33 Mn 0.33 O2 and conductive agent SuperP were mixed into a slurry in a mass ratio of 10:85:5, coated on an aluminum foil current collector, and dried in a vacuum oven at 110°C for 20 hours. The resulting pieces were cut into lithium-rich manganese-based positive electrode sheets, and the product was recorded as CMC.

[0046] like Figure 7 and Fig.11 As shown in the SEM images of the products prepared in Example 1 and Comparative Example 1 of the present invention, Figure 7 and Fig.11 It can be seen that after the introduction of the mixed ion-electron conductivity aqueous binder, the surface of the lithium-rich manganese is uniform and flat. In contrast, the surface of the electrode prepared using sodium carboxymethyl cellulose has obvious cracks.

[0047] Comparative Example 2

[0048] Step 1: Add 1 g of sodium lignin sulfonate and 1 g of sodium carboxymethyl cellulose stepwise into 98 g of deionized water, and stir at 300 rpm for 24 hours at room temperature to prepare a uniform and transparent sodium lignin sulfonate-sodium carboxymethyl cellulose solution;

[0049] Step 2: Lithium-rich manganese positive electrode material 0.5Li2MnO3·0.5LiNi 0.33 Co 0.33 Mn 0.33 O2, conductive agent SuperP, and sodium lignin sulfonate-sodium carboxymethyl cellulose solution binder are uniformly mixed in a mass ratio of 85:5:10 to prepare a slurry, coated on an aluminum foil current collector, and dried in a vacuum oven at 110°C for 20 hours, and then cut into pieces to obtain lithium-rich manganese-based positive electrode sheets.

[0050] Comparative Example 3 Preparation of Binder from Carrageenan and Sodium Carboxymethyl Cellulose

[0051] Step 1: Add 1 g of carrageenan and 1 g of sodium carboxymethyl cellulose stepwise into 98 g of deionized water, and stir at 300 rpm for 24 hours at room temperature to prepare a uniform and transparent carrageenan-sodium carboxymethyl cellulose solution;

[0052] Step 2: Lithium-rich manganese positive electrode material 0.5Li2MnO3·0.5LiNi 0.33 Co 0.33 Mn 0.33O2, conductive agent SuperP, and carrageenan-sodium carboxymethyl cellulose solution binder are uniformly mixed in a mass ratio of 85:5:10 to prepare a slurry, coated on an aluminum foil current collector, and dried in a vacuum oven at 110°C for 20 hours. The resulting pieces are then cut to obtain a lithium-rich manganese-based positive electrode sheet, denoted as CC11.

[0053] like Figure 6 , Fig.10 and Figure 3 The electrochemical impedance diagrams of the electrodes of Example 1, Comparative Example 1 and Comparative Example 3 before cycling are shown. Figure 6 , Fig.10 and Figure 3 By comparison, adding polyelectrolyte can reduce the electrode impedance, and continuing to add conductive polymer further reduces the electrode impedance.

[0054] Comparative Example 4

[0055] Step 1: Add 2 g of sodium carboxymethyl cellulose to 98 g of deionized water, and stir at 300 rpm for 24 hours at room temperature to prepare a sodium carboxymethyl cellulose solution;

[0056] Step 2: Take 1g of sodium carboxymethyl cellulose solution, add 20μL of pyrrole monomer, stir at 300rpm for 5 minutes, then add 10mg of ammonium sulfate and stir at 50rpm overnight (12h) at room temperature for polymerization to obtain a composite binder;

[0057] Step 3: Lithium-rich manganese positive electrode material 0.5Li2MnO3·0.5LiNi 0.33 Co 0.33 Mn 0.33 O2, conductive agent SuperP, and the composite binder of step 2 are uniformly mixed in a mass ratio of 90:2:8 to prepare a slurry, coated on an aluminum foil current collector, and dried in a vacuum oven at 110°C for 20 hours, and then cut into pieces to obtain a lithium-rich manganese-based positive electrode sheet.

[0058] Comparative Example 5

[0059] Step 1: dissolve 2 g of sodium lignin sulfonate in 98 g of deionized water and stir for 24 hours to obtain a sodium lignin sulfonate solution;

[0060] Step 2: Use the prepared sodium lignin sulfonate solution as a binder and the lithium-rich manganese positive electrode material 0.5Li2MnO3·0.5LiNi 0.33 Co 0.33 Mn 0.33 O2 and conductive agent SuperP were mixed into a slurry in a mass ratio of 10:85:5, coated on an aluminum foil current collector, and dried in a vacuum oven at 110°C for 20 hours. The slurry was then cut into pieces to obtain a lithium-rich manganese-based positive electrode sheet.

[0061] The positive electrode sheet of Example 1 or Comparative Examples 1-5 is used, a metal Li sheet is used as a reference electrode and a counter electrode, a Celgard-2400 is used as a diaphragm, and the electrolyte is Xinzhoubang 3045I. The assembly is carried out in a glove box filled with argon gas with oxygen and water content less than 0.01ppm. Its electrochemical performance is tested for charge and discharge using a 2025 button battery on a Xinwei test system, and the test voltage window is 2.0-4.8V. The test temperature is 27±1℃, and the first three cycles are activated at a rate of 0.1C (1C=200mAh / g), and the 1C rate cycle is used from the 4th cycle. The performance test results are listed in Table 1.

[0062] Table 1

[0063]

[0064]

[0065] Comparison of Comparative Example 1 and Comparative Example 2 shows that the introduction of polyelectrolyte improves the first-cycle coulombic efficiency, the first-cycle discharge capacity reaches 294.64 mAh / g, and the cycle stability is also improved;

[0066] Comparison of Comparative Examples 1, 2 and 3 shows that the introduction of carrageenan and sodium lignin sulfonate containing sulfonic acid groups improves the electrochemical performance of the electrode, and the first-cycle discharge specific capacity and cycle stability are improved; Comparison of Comparative Examples 2 and 3 shows that although sodium lignin sulfonate also contains sulfonic acid groups, its electrochemical performance is not as good as that of carrageenan, which may be due to the large number of hydroxyl groups on carrageenan, which improves the bonding performance and toughness of the binder to a certain extent;

[0067] Comparison of Comparative Example 1 and Comparative Example 4 shows that the introduction of the conductive polymer formed by the polymerization of the pyrrole monomer can improve the first cycle coulombic efficiency and the first cycle discharge capacity, but the cycle stability is relatively poor. Comparison of Example 1 and Comparative Example 3 shows that the introduction of the conductive polymer further improves the first cycle coulombic efficiency. In Example 1, the introduction of carrageenan and the conductive polymer at the same time can better improve the discharge capacity and cycle stability of the battery, and the effect is significant, and the two have a synergistic effect.

[0068] From Table 1, it can be seen that the first-cycle coulombic efficiency of the battery made of the high-conductivity and lithium-conducting composite binder of Example 1 of the present invention (1g carrageenan and 1g carboxymethyl cellulose, 20μL pyrrole monomer added, 10mg ammonium sulfate) reaches 87.61%; at the same time, the battery made of the high-conductivity and lithium-conducting composite binder has the best discharge specific capacity and cycle stability, the first-cycle discharge capacity at 0.1C reaches 297.84mAh / g, the first-cycle discharge capacity at 1C reaches 220.9mAh / g, and the 300-cycle capacity retention rate is as high as 91.32%.

[0069] The above are only specific embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a highly conductive lithium-conductive composite aqueous binder for high-voltage positive electrode materials, characterized in that: The specific steps are as follows: Step 1: Prepare carrageenan-sodium carboxymethyl cellulose solution Add carrageenan to deionized water, mix well, then add sodium carboxymethyl cellulose, the mass ratio of carrageenan, sodium carboxymethyl cellulose and deionized water is 1:1:98, stir and mix at room temperature for 24 hours to prepare a carrageenan-sodium carboxymethyl cellulose solution; Step 2: Preparation of high-conductivity lithium-conducting composite binder Take carrageenan-sodium carboxymethyl cellulose solution and add pyrrole monomer, the mass volume ratio of the carrageenan-sodium carboxymethyl cellulose solution to the pyrrole monomer is 100:2g / mL, stir and mix at room temperature for 5 minutes, add initiator, the mass ratio of the initiator to the carrageenan-sodium carboxymethyl cellulose solution is 1:100, stir and polymerize at room temperature overnight to obtain a high-conductivity lithium-conducting composite water-based composite binder. Furthermore, the initiator is ammonium sulfate.

2. The method for preparing a highly conductive lithium-conductive composite aqueous binder for high-voltage positive electrode materials according to claim 1, characterized in that: When stirring and mixing, the stirring speed is 300 rpm.

3. The method for preparing a highly conductive lithium-conductive composite aqueous binder for high-voltage positive electrode materials according to claim 1, characterized in that: Stir overnight at room temperature for 12 h.

4. Use of the aqueous binder as claimed in claim 1 in a positive electrode sheet of a lithium ion battery.

5. The use of the aqueous binder according to claim 4 in a positive electrode sheet of a lithium ion battery, characterized in that: The lithium-ion battery positive electrode plate is a lithium-manganese-rich positive electrode plate.

6. The use of the aqueous binder according to claim 5 in a positive electrode sheet of a lithium ion battery, characterized in that: The preparation of the positive electrode plate of the lithium ion battery is as follows: The active material, conductive agent and binder are uniformly mixed to prepare a slurry, which is then coated on an aluminum foil and dried in a vacuum oven at 110° C. for 20 hours to obtain a lithium-rich manganese-based positive electrode sheet.

7. The use of the aqueous binder according to claim 6 in a positive electrode sheet of a lithium ion battery, characterized in that: The mass ratio of the active material, the conductive agent and the binder is 85:5:10.

Citation Information

Cited By

  • Carboxymethyl cellulose derivative as well as preparation method and application thereof

    CN119874944A